Faktor-Faktor Kepuasan Pasien dengan Sisa Makanan pada Pelayanan Gizi di Rumah Sakit Islam Arafah Rembang - Noor Rochmah; Sufiati Bintanah; Erma Handarsari (Universitas Muhammadiyah Semarang, 2018)
Background : One of the success of food serving at the hospital is patient satisfaction. Lower patient satisfaction has an influence on how patient will be eat and left the food. The object of the study is to know the correlation of patient satisfaction factors and food waste at Arafah Islamic Hospital Rembang. Method : This study used observational analytic with an across sectional approach. The population are all patient at Musdalifah room and Dzulkhulaifah room of Arafah Islamic Hospital Rembang with sample criteria, at least 2 days was treated and got a normal and soft food. Thesample of this study are 31 respondents used consecutive sampling. The instruments used are questionnaire and Comstock form. The normality test of the data usedKolmogorof -Smirnov test.The statistical test used is Rank-Spearman test. Results : This study found all of the respondents 100% of exact food time distribution. Most respondents 77, 4 % that said a variation of the food. 48, 8 % said the taste is delicious. All of the respondent (100%) the food equipments are clean and the server is friendly. Most respondents 83, 9% attractive for the served food. Food waste from breakfast : main course 6,5%, animal side dish 3,2%, vegetable side dish 16,5%, vegetables 9,7%. At lunch: main course 6,5%, animal side dish 3,2%, vegetable side dish 12,9%, vegetables19,4%. At dinner: main course 3,2%, animal side dish 9,7%, vegetable side dish 12,9%, vegetables 9,7%. There is no correlation between menu variationwith food waste but, the relation between animal side dish and food waste at breakfast has a correlation value p=0, 037. There is no correlation between the taste of the food and food waste (p> 0, 05). There is no correlation between appearance of food and food waste but the relation between animal side dish and food waste at breakfast has correlation value p=0, 038. Keywords: The Patient Satisfaction’s Factors, food waste, taste of food, appearance of food